Effects of heat and hypoxia training on the fat oxidation capacity of competitive athletes - Geng, Z.; Wu, X.; Wang, J.; Cao, G.; Tan, C.; Li, L.; Qiu, J. (European Journal of Sport Science, 2025)
This study aimed to evaluate the impact of a four-week heat and hypoxia training on the fat oxidation capacity of competitive athletes. Eight elite male modern pentathlon athletes completed a four-week aerobic endurance training program in three environments: normal (CON), high temperature and humidity (HOT), and hypoxia (HYP). Assessments were conducted in both the normal environment and the corresponding special environment before and after training. Gas exchange data were collected during exercise to assess aerobic capacity, and fat oxidation was measured using indirect calorimetry. Fat oxidation kinetics were modeled using the sinusoidal (SIN) mathematical model to determine the maximum fat oxidation (MFO) and the exercise intensity at which it occurred (FATmax). Under normal environment, HOT training had an increase in absolute VO2 (238.152 mL/min and p = 0.003), both the HOT (96.062 s and p = 0.006) and HYP (109.917 s and p = 0.002) trainings demonstrated increases in VT2@Time, both the HOT (0.126 g/min and p = 0.015) and HYP (0.157 g/min and p = 0.004) trainings showed increases in MFO, and the HOT training also exhibited an increase in FATmax (5.303 g/min and p = 0.005); both the HOT and HYP trainings showed dilatation of the fat oxidation curve, with the HOT training also displaying dilatation in the fat oxidation curve under heat conditions. Four-weeks of heat and hypoxia training significantly enhanced athletes' aerobic metabolism and fat oxidation capacity. The benefits of heat training on aerobic metabolism and fat oxidation may exceed those of hypoxia training.